2016
DOI: 10.1042/bcj20160393
|View full text |Cite
|
Sign up to set email alerts
|

Selenophosphate synthetase 1 is an essential protein with roles in regulation of redox homoeostasis in mammals

Abstract: Selenophosphate synthetase (SPS) was initially detected in bacteria and was shown to synthesize selenophosphate, the active selenium donor. However, mammals have two SPS paralogs, which are designated SPS1 and SPS2. Although it is known that SPS2 catalyzes the synthesis of selenophosphate, the function of SPS1 remains largely unclear. To examine the role of SPS1 in mammals, we generated a Sps1 knockout mouse and found that systemic SPS1 deficiency led to embryos that were clearly underdeveloped by E8.5 and vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 50 publications
(69 reference statements)
1
45
0
Order By: Relevance
“…5e), are also involved in ROS-mediated apoptosis 25 . RNA-Seq data also showed that negative regulators of ROS ( aplnrb , hsp70.3 , sephs1 and dkc1 ) 2629 were downregulated in unfit cells, whereas positive regulators ( fabp3 , ptgdsb.1 and krt8 ) 3032 were upregulated (Fig. 5a and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…5e), are also involved in ROS-mediated apoptosis 25 . RNA-Seq data also showed that negative regulators of ROS ( aplnrb , hsp70.3 , sephs1 and dkc1 ) 2629 were downregulated in unfit cells, whereas positive regulators ( fabp3 , ptgdsb.1 and krt8 ) 3032 were upregulated (Fig. 5a and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 81%
“…6). Co-expression of the ROS negative regulators SOD1 33 or Sephs1 29 , or smad4 knockdown reduced ROS and DNA-oxidization levels in β-catCA-expressing cells (Fig. 6b, c).…”
Section: Resultsmentioning
confidence: 89%
“…Selenide water dikinase ( SelD ; FBgn0261270; BDSC 29553) encodes a member of the selenophosphate synthetase 1 (SPS1) enzyme family that does not synthesize selenophosphate but rather functions in redox homeostasis and glutathione metabolism (Xu et al 2007a; Xu et al 2007b; Tobe et al 2016). Consistent with the proposed functions of SPS1 proteins, SelD serves a critical role in Drosophila eye development by restricting reactive oxygen species (ROS) accumulation (Morey et al 2003).…”
Section: Resultsmentioning
confidence: 99%
“…brucei ER stress. On the other hand, it is also possible that the only selenophosphate synthetase isoform observed in trypanosomatids ( Tb SPSH2) has a more direct role in redox homeostasis in the cell as suggested for the mammalian SEPHS1 [ 69 ].…”
Section: Discussionmentioning
confidence: 99%